SIMULATING THE EFFECTS OF WATERSHED DEMARCATION ON THE PREDICTION OF NUTRIENTS AND HYDROLOGICAL YIELD USING SWAT MODEL - ADEOGUN, Adenyi Ganiyu; Bello, Abubakar Abdulsalam; Amoo, Oseni Taiwo; Ayeh, Ayomide Abdulbaqi (Journal of Engineering and Technology (JET), 2025)
Watershed delineation is a crucial step in hydrological modeling, as it determines the accuracy of flow and nutrient transport predictions. This study investigated the impact of watershed delineation on the prediction of nutrients, surface runoff, and groundwater yield at the upstream section of Asa Dam River system, Ilorin, Kwara State, Nigeria. The MapWindowGIS was used to pre-process spatial data (Digital Elevation Model, Land use and Soil data) and the Soil and Water Assessment Tool (SWAT) was used to predict organic phosphorus, nitrate nutrients, surface runoff, and groundwater yield at the upstream outlet in the Asa River catchment. The catchment was delineated into 5, 9, 13, 15, 17, and 29 sub-catchments, and each routed sub-catchment was simulated using the temporal and spatial data of the study area. The predicted annual values for organic phosphorus and nitrate concentrations showed an increase from 0.734 mg/l to 6.76 mg/l and from 1.44 mg/l to 3.57 mg/l, respectively, as the watershed delineation expanded from 5 to 29 sub-basins. However, the number of sub-basin divisions had little to no effect on the average monthly predicted values for nutrients and the resulting water yield in the catchment. The simulated results indicated that the number of sub-catchment divisions significantly influenced the annual predicted values for nutrients, sediment, and streamflow yield. The monthly results for organic phosphorus and nitrate concentration for sub-catchments delineation showed no effect for surface runoff, groundwater, and water yield quantification. The outcome of this research has important implications for water resource management and policy development, especially in addressing water quality issues within the Asa Dam River watershed.